The Logic and Language of Classic Grounded Theory - Alvita Nathaniel (Grounded Theory Review: An International Journal, 2023)
Although it is not clearly understood by many, classic grounded theory utilizes deduction, induction, and abduction as the necessary logic functions of the research process. Glaser’s described the forms of logic—induction, abduction, and deduction—but referred to them as conceptualization, theoretical coding, and theoretical sampling. Induction begins with data and produces concepts, which are the building blocks of grounded theory. Employing abduction, the analyst infers relationships among the concepts to develop interrelated hypotheses. Deduction is used to gather data to fill in the gaps and produce an explanatory theory. Each type of logic is indispensable to classic grounded theory method. The purpose of this methodological paper is to briefly describe the process and product of each type of logic as applied to the language and procedures of classic grounded theory.